From Fratricide to Forgiveness: The Ethics of Anger in Genesis - Schlimm, Matthew Richard (Tyndale bulletin, 2010)
A dissertation showing both how anger functions as a literary motif in Genesis and how this book offers moral guidance for engaging this emotion.